Effect of SiO2/BaO ratio on sintering behavior, crystallization behavior, and properties of SrO–BaO–B2O3–SiO2 glass-ceramics. Issue 13 (1st July 2021) - Zhang, Bing; He, Feng; Cao, Xiuhua; Ren, Haidong; Yan, Dongyang; Xie, Junlin
Abstract: SrO–BaO–B2 O3 –SiO2 glass-ceramics with a high dielectric constant and low dielectric loss were prepared. The influence of the SiO2 /BaO ratio on the sintering behavior, crystallization behavior, and properties were systematically investigated. The results showed that the increasing amount of liquid phase from increasing the SiO2 /BaO ratio promoted sintering, resulting in an initial decrease in the sintering activation energy. However, the viscosity of the liquid phase continued to increase, leading to an increase in the sintering temperature and sintering activation energy when the SiO2 /BaO ratio reached 0.90. As the SiO2 /BaO ratio increased, the fraction of the primary phase BaSi2 Al2 O8 increased, and its grains grew; the minor phase SrTiO3 was suppressed, resulting in changes in the properties of the glass-ceramics. The sample with a SiO2 /BaO ratio of 0.69, which was sintered at 850 °C for 10 min, showed excellent properties: a coefficient of thermal expansion (CTE) of 10.63 × 10 −6 K −1 (25–500 °C), a dielectric constant (ϵr ) of 16.24 (1 MHz), a dielectric loss (tanδ) of 3.39 × 10 −3 (1 MHz), a flexural strength of 138.80 MPa, and a quality loss of acid corrosion of 1.06 × 10 −4 g mm −2 . The results indicated that the SrO–BaO–B2 O3 –SiO2 glass-ceramics used in this study have great potential for low-temperature co-fired ceramics applications.